Pengaruh Work-life balance, Beban Kerja, Motivasi Kerja Terhadap Kinerja Pegawai Diperusahaan Perbankan - Akbar, Bintang (House of Management and Business (HOMBIS) Journal, 2025)
The high intensity of work and the complexity of roles in the banking industry make aspects such as Work-life balance, workload pressure, and work motivation crucial to examine employee performance. This study employs a quantitative approach with a descriptive-associative design, involving 100 participants from the Greater Jakarta area (Jabodetabek). It is analyzed using the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS). The findings reveal a significant positive relationship between Work-life balance and employee performance. In addition, Work-life balance significantly reduces workload, although it does not directly influence work motivation. While neither workload nor motivation directly impacts performance, both act as mediators in the indirect relationship between Work-life balance and employee performance. Therefore, it can be concluded that Work-life balance plays a strategic role—both directly and indirectly—in influencing employee performance through perceptions of workload and intrinsic motivation, which should be considered in human resource management practices within the financial services sector.